SPATIO-TEMPORAL ANALYSIS OF THE GEOSYSTEMS OF THE TENIZ-KORGALZHYN DEPRESSION BASED ON THE DATA DECIPHERED FROM LANDSAT AND SENTINELSATELLITE IMAGES - E. N. Sagatbaev,; A. N. Dunets, (Academic Journal of Physical and Chemical Sciences, 2019)
Studies of the geosystems of the Teniz-Korgalzhyn depression were carried out. The spatial and temporal patterns of the structure, functioning, and dynamics of the development of the landscape components of the territory under study are determined on the basis of computer-aided decoding of multizone space images. With the use of the functionality of modern instrumental GIS and decoding algorithms, the indicators of productivity of geosystems and the anthropogenic transformation are determined. Significant differences in the anthropogenic factor have been established, which have local rather than ubiquitous effects on the dynamics of geosystems against the background of significant changes in the ratio of moisture and productivity. In the last chapter, conclusions are made about the need to control anthropogenic influence and to ensure the rational use of resources of the territory as a factor of sustainable development.